2010
DOI: 10.1016/j.chemosphere.2010.05.015
|View full text |Cite
|
Sign up to set email alerts
|

Chemical state of boron in coal fly ash investigated by focused-ion-beam time-of-flight secondary ion mass spectrometry (FIB-TOF-SIMS) and satellite-transition magic angle spinning nuclear magnetic resonance (STMAS NMR)

Abstract: The chemical states of boron in coal fly ash, which may control its leaching into the environment, were investigated by focused-ion-beam time-of-flight secondary ion mass spectrometry (FIB-TOF-SIMS) and satellite-transition magic angle spinning nuclear magnetic resonance (STMAS NMR) spectroscopy. The distribution of boron on the surface and in the interior of micron-sized fly ash particles was directly observed by FIB-TOF-SIMS. Coordination numbers of boron and its bonding with different atoms from particles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…However, chemical maps are good indicators of relative surface concentration and its change as a function of sample treatment or time. In previous researches this technique provided information on the elemental distributions not only at the surface but also inside the particles (Hayashi et al, 2010). In the present work, generally the composition of this kind of CFAs samples, which are often very complex, included the detection of light elements, heavy metals, and hydrocarbons.…”
Section: Fly Ash Characterization By Tof-simsmentioning
confidence: 99%
“…However, chemical maps are good indicators of relative surface concentration and its change as a function of sample treatment or time. In previous researches this technique provided information on the elemental distributions not only at the surface but also inside the particles (Hayashi et al, 2010). In the present work, generally the composition of this kind of CFAs samples, which are often very complex, included the detection of light elements, heavy metals, and hydrocarbons.…”
Section: Fly Ash Characterization By Tof-simsmentioning
confidence: 99%
“…Iwashita mentioned that under highly alkaline conditions, the leaching of B and Se tended to decrease [3]. Shun-ichi stated that coal fly ash with better leaching characteristics contained boron in the CaO-and MgO-phases on the surface of coal fly ash particles [8]. Jose and Wang reported that alkaline pH, calcium addition, temperature and the leaching time affected the leaching of As and Se [4,9].…”
Section: Ca(oh) 2 Ps Ash 8 and Bf Cement As Single Additivesmentioning
confidence: 99%
“…Trace elements that are also classified as heavy metals are transformed into less soluble compounds, which makes these trace elements non-hazardous in the environment. As, Se, B, and F can react with calcium and form relatively insoluble compounds such as Ca 3 (AsO 4 ) 2 , Ca 4 (OH) 2 (AsO 4 ) 2 •4H 2 O [9,13], CaSeO 3 [9], Ca 2 B 2 O 5 , Ca 3 B 2 O 6 [8] and CaF 2 [24,25]. Therefore, calcium addition through the use of high-calcium-content materials in the leaching process could be applied to control the leaching of trace elements.…”
Section: Ca(oh) 2 Ps Ash 8 and Bf Cement As Mixed Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…31) These phenomena were not observed in sorption of fluoride on MgO. 26,27) Other phases such as Mg 7 Fig. 4, although the reliability of identification is relatively low with these index cards.…”
Section: Resultsmentioning
confidence: 99%